2015
DOI: 10.1175/jtech-d-14-00172.1
|View full text |Cite
|
Sign up to set email alerts
|

Observational Perspectives from U.S. Climate Reference Network (USCRN) and Cooperative Observer Program (COOP) Network: Temperature and Precipitation Comparison

Abstract: The U.S. Cooperative Observer Program (COOP) network was formed in the early 1890s to provide daily observations of temperature and precipitation. However, manual observations from naturally aspirated temperature sensors and unshielded precipitation gauges often led to uncertainties in atmospheric measurements. Advancements in observational technology (ventilated temperature sensors, well-shielded precipitation gauges) and measurement techniques (automation and redundant sensors), which improve observation qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…It is also important for climate change analyses over the cold regions. Leeper et al (2015), in comparison of USCRN with the COOP station network precipitation measurements, averaged the USCRN hourly temperature data during precipitation periods into an event mean and used it to group precipitation events into warm (mean temperature > 5 • C), near-freezing (mean temperature between 0 and 5 • C), and freezing (mean temperature < 0 • C) conditions. Yang et al (2005) used the daily mean air temperature to estimate precipitation types (snow, mixed, and rain) when this information was not available for the northern regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important for climate change analyses over the cold regions. Leeper et al (2015), in comparison of USCRN with the COOP station network precipitation measurements, averaged the USCRN hourly temperature data during precipitation periods into an event mean and used it to group precipitation events into warm (mean temperature > 5 • C), near-freezing (mean temperature between 0 and 5 • C), and freezing (mean temperature < 0 • C) conditions. Yang et al (2005) used the daily mean air temperature to estimate precipitation types (snow, mixed, and rain) when this information was not available for the northern regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Efforts have been reported to examine the precipitation discontinuity within a country (Groisman and Easterling, 1994;Sanderson, 1975). Leeper et al (2015) found that the US Cooperative Observer Program (COOP) Network stations reported slightly more precipitation overall (1.5 %), with network differences varying seasonally. The COOP gauges were sensitive to wind biases, particularly over winter when COOP observed (10 %) less precipitation than the US Climate Refer- ence Network (USCRN).…”
Section: Introductionmentioning
confidence: 99%
“…Several networks remarked upon completion that the exercise had been useful and had led to discussions around potential innovations or improvements which could yield increased assessment scores in any future assessment but, more importantly, increase accessibility, usability and robustness of their measurement systems. This benefit was felt most strongly for those networks with a central mission to provide the highest possible quality measurements such as USCRN (Diamond et al, 2013;Leeper et al, 2015), TCCON, NDACC and EARLINET. For example, the results of the NDACC assessment were discussed in depth at their most recent annual meeting and this led to several suggestions for improvements.…”
Section: Critical Reflection On the Exercise Outcomes And Limitationsmentioning
confidence: 99%
“…However, recent research comparing USCRN with COOP stations indicate gauge evaporation can bias observations even when taken frequently at a sub-hourly rate (Leeper et al, 2015a). The USCRN monitors precipitation at a 5 min frequency from a well-shielded automated funnel-less gauge whereas COOP stations operate a manual funnel-capped gauge that is checked daily.…”
Section: Check Description Constraintmentioning
confidence: 99%